2021
DOI: 10.1093/nar/gkaa1228
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal differentiation involves cleavage of histone H3 N-terminal tails by multiple proteases

Abstract: The proteolytic cleavage of histone tails, also termed histone clipping, has been described as a mechanism for permanent removal of post-translational modifications (PTMs) from histone proteins. Such activity has been ascribed to ensure regulatory function in key cellular processes such as differentiation, senescence and transcriptional control, for which different histone-specific proteases have been described. However, all these studies were exclusively performed using cell lines cultured in vitro and no cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
(33 reference statements)
5
12
0
Order By: Relevance
“…Third, Marruecos et al investigate a direct interaction with another essential cell signaling molecule, i.e., IkBa. Finally, the findings reported here are coherent with the few common notions about histone clipping (Dhaenens et al , 2015): (i) Histone clipping is strongly associated with developmental transitions (Duncan et al , 2008; De Clerck et al , 2019; Ferrari et al , 2021); (ii) proteins that can cleave histones have all been known for very different functions and are most often not associated with nuclear localization; (iii) hPTMs might regulate the clipping (Duncan et al , 2008; Ferrari et al , 2021); and (iv) very plausibly, clipping is part of a complex regulatory system that has a lot of redundancy (Duncan et al , 2008; Dhaenens et al , 2015; Ferrari et al , 2021). This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021).…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationsupporting
confidence: 89%
See 1 more Smart Citation
“…Third, Marruecos et al investigate a direct interaction with another essential cell signaling molecule, i.e., IkBa. Finally, the findings reported here are coherent with the few common notions about histone clipping (Dhaenens et al , 2015): (i) Histone clipping is strongly associated with developmental transitions (Duncan et al , 2008; De Clerck et al , 2019; Ferrari et al , 2021); (ii) proteins that can cleave histones have all been known for very different functions and are most often not associated with nuclear localization; (iii) hPTMs might regulate the clipping (Duncan et al , 2008; Ferrari et al , 2021); and (iv) very plausibly, clipping is part of a complex regulatory system that has a lot of redundancy (Duncan et al , 2008; Dhaenens et al , 2015; Ferrari et al , 2021). This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021).…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationsupporting
confidence: 89%
“…Finally, the findings reported here are coherent with the few common notions about histone clipping (Dhaenens et al , 2015): (i) Histone clipping is strongly associated with developmental transitions (Duncan et al , 2008; De Clerck et al , 2019; Ferrari et al , 2021); (ii) proteins that can cleave histones have all been known for very different functions and are most often not associated with nuclear localization; (iii) hPTMs might regulate the clipping (Duncan et al , 2008; Ferrari et al , 2021); and (iv) very plausibly, clipping is part of a complex regulatory system that has a lot of redundancy (Duncan et al , 2008; Dhaenens et al , 2015; Ferrari et al , 2021). This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021). However, one aspect of clipping is very different this time: Despite its dramatic nature, inhibition of clipping rarely inhibits cell transition (Duncan et al , 2008), yet in the current work (Marruecos et al , 2021) and in Ferrari et al, (2021), it is shown for the first time that trypsin inhibition can block intestinal differentiation effectively.…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationsupporting
confidence: 89%
“…In contrast, DCM gene body labelling of canonical PRC1 members Cbx2,4,6,7 and 8 was below background levels, indicating that involvement of PRC1 in ISC maintenance is mediated through ncPRC1 complexes (Fig 5a)(Blackledge et al, 2014). To investigate the role of PRC1 and PRC2 in promoter and enhancer regulation during ISC to enterocyte differentiation, we examined enrichment of H2A119ub or H3K27me3, catalysed by PRC1 and PRC2 respectively, using ISC, crypt and enterocyte ChIP-seq data sets (Chiacchiera et al, 2016a; Ferrari et al, 2021). This analysis revealed a lack of enrichment of both H2Aub119 and H3K27me3 at enhancers at any stage of ISC differentiation (Fig 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic marking and histone clipping have been shown to be recovered in spheroids [38] and this has been shown to occur during intestinal differentiation in vivo [50]. Metabolic reprogramming,which may be a key change during cancer development is also demonstrated in 3D spheroids [9].…”
Section: Applicationsmentioning
confidence: 97%